PS-BPP06-2: ASSOCIATIONS BETWEEN URIC ACID LEVELS AND HYPERTENSION INCIDENCE IN AN APPARENTLY HEALTHY JAPANESE POPULATION. (January 2023) - Salim, Anwar Ahmed; Kawasoe, Shin; Kubozono, Takuro; Ojima, Satoko; Kawabata, Takeko; Ikeda, Yoshiyuki; Miyahara, Hironori; Tokushige, Koichi; Ohishi, Mitsuru
Abstract : Objective: Uric acid (UA) has been linked to the development of hypertension. However, it is not known if this association is significant in men and women who are apparently healthy at baseline. Design and Methods: This retrospective cohort study included individuals who participated in a health checkup at the Kagoshima Kouseirin Hospital from October 2008 to April 2019. We excluded participants with hypertension, diabetes, dyslipidemia, obesity, estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73m2, history of gout, hyperuricemia medication, and missing data at baseline. To assess the association between baseline UA levels and 5 year hypertension incidence, we performed univariable and multivariable logistic regression analysis by sex according to their UA quartiles as follows: In men: 1st quartile ≧ 4.8 mg/dL, 2nd quartile 4.9 to 5.6 mg/dL, 3rd quartile 5.7 to 6.4 mg/dL, and 4th quartile ≧ 6.5 mg/dL; In women: 1st quartile ≧ 3.4 mg/dL, 2nd quartile 3.5 to 4.0 mg/dL, 3rd quartile 4.1 to 4.7 mg/dL, and 4th quartile ≧ 4.8 mg/dL. The ORs were adjusted for age, body mass index, systolic blood pressure (SBP), diastolic blood pressure (DBP), current smoking, alcohol consumption, exercise habit, serum triglyceride, low density lipoprotein cholesterol, high density lipoprotein cholesterol, fasting plasma glucose and eGFR. Hypertension incidence was defined as SBP ≧ 140 mmHg and/or DBP ≧ 90 mmHg at follow up, or newly prescribed antihypertensive medication during 5 years of follow up. Results: In total, 21, 514 participants (age, 52.9 ± 10.9 years; men, 39.8%), were enrolled. During the 5 year of follow-up, 1415 (16.5%) men and 1408 (10.9%) women developed hypertension. In univariable analysis, the UA levels were significantly associated with hypertension in both men (OR for fourth to first quartile, 1.45; 95% confidence interval [CI], 1.24 to 1.70, P < 0.0001) and women (OR for fourth to first quartile, 1.62; 95%CI, 1.38 to 1.90, P < 0.0001). After adjusting for covariates, the UA levels were significantly associated with hypertension in men (OR for fourth to first quartile, 1.35; 95%CI, 1.13 to 1.62, P = 0.0011), but was not in women (OR for fourth to first quartile, 1.14; 95%CI, 0.95 to 1.36, P = 0.1541) Conclusion: Elevated UA levels are associated with hypertension incidence in Japanese men without hypertension, diabetes, dyslipidemia, obesity, and decreased kidney function.